Spontaneous disappearance of high titre factor VIII inhibitor 15 years after unsuccessful ITI - Thom, K.; Male, C.; Falger, J.; Pabinger, I. (Hämostaseologie, 2009)
The most serious complication of haemophilia A is development of a high-titre factor VIII (FVIII) inhibitor which renders the patient unresponsive to FVIII replacement. Bleeding complications can only be controlled using FVIII-inhibitor bypassing agents but their effect is less certain. The ultimate goal is to eliminate the inhibitor by immune tolerance induction therapy (ITI) using daily high doses of FVIII. The success rate of ITI using various protocols is between 56 and 79% (1, 2). If ITI is unsuccessful, the inhibitor usually persists throughout life.We report on a patient with a high titre FVIII inhibitor that persisted after ITI but spontaneously disappeared 15 years later.
Keywords: Haemophilia A; FVIII inhibitor; immune tolerance induction